Sliding Walk With Friction Control of Double-Network Gel on Feet of Inchworm Robot - Takagi, Minoru; Yoshida, Kazunari; Hoshino, Hiroyuki; Tadakuma, Riichiro; Suzuri, Yoshiyuki; Furukawa, Hidemitsu (Frontiers in Mechanical Engineering, 2019)
Soft-matter robotics, which is named for robots made from soft materials, will possibly conquer the limit of conventional rigid body dynamics of hard robots made from hard materials. For example, a snake-like robot, of which body is made from soft materials, will walk in various environments including narrow space like drain pipes with complicated structure. Here we developed a walking robot with the friction control of double-network hydrogel (DN gel) on its feet, as the first model based on the concept of the soft-matter robotics. It is found that with appropriate control of the friction of DN gel, the inchworm walking robot has realized its high enough velocity for pipe inspection. We discussed the physical principle of the walking motion of the inchworm search robot and its actual mechanism to provide thrust for its walking motion.